Predictive Value of Lung Ultrasound Scores Combined with Serum ANGPTL4 Levels on Severity and Prognosis of Neonatal Respiratory Distress Syndrome - Wang L; Ji P; Yin J; Xue M; Wang J; Wan Y; Dong B (International Journal of General Medicine)
Liangfu Wang,1 Ping Ji,2 Jiansong Yin,2 Mei Xue,2 Jing Wang,3 Yu Wan,2 Baoqiang Dong4 1Department of Soft Traumatology of Integrated Chinese and Western Medicine, Shenyang Fourth People’s Hospital, Shenyang, Liaoning, 110031, People’s Republic of China; 2Neonatal Intensive Care Unit, Second People’s Hospital of Changzhou Affiliated to Nanjing Medical University, Changzhou, Jiangsu, 213164, People’s Republic of China; 3Department of Child Healthcare, Second People’s Hospital Changzhou Affiliated to Nanjing Medical University, Changzhou, Jiangsu, 213164, People’s Republic of China; 4College of Acupuncture and Massage, Liaoning University of Traditional Chinese Medicine, Shenyang, Liaoning, 110000, People’s Republic of ChinaCorrespondence: Baoqiang Dong, College of Acupuncture and Massage, Liaoning University of Traditional Chinese Medicine, No. 77 Chongshan East Road, Huanggu District, Shenyang, Liaoning, 110000, People’s Republic of China, Tel +86-024-31207001, Email DongBaoqiang3071@163.comObjective: Respiratory distress syndrome threatens neonates’ life. This study probed the predictive value of lung ultrasound scores combined with serum angiopoietin-like protein 4 (ANGPTL4) levels on neonatal respiratory distress syndrome (NRDS) severity and prognosis.Methods: The NRDS group (n = 115) and control group (n = 30) were established. In both groups, lung ultrasound scores and serum ANGPTL4 levels, lung ultrasound scores and serum ANGPTL4 levels of newborns with NRDS of different severity, the risk factors affecting the poor prognosis of NRDS neonates, and the value of serum ANGPTL4 levels combined with lung ultrasound scores in determining the severity and prognosis of newborns with NRDS were analyzed.Results: The NRDS groups had higher lung ultrasound scores and serum ANGPTL4 levels, and lower Apgar scores than the control group; lung ultrasound scores and serum ANGPTL4 levels were higher in the moderate and severe groups than in the mild group, and those were higher in the severe group than in the moderate group (all p < 0.05). The logistic regression analysis showed that high lung ultrasound scores, and high serum ANGPTL4 levels were risk factors for NRDS poor prognosis (OR > 1, p < 0.05), and high Apgar scores are the protective factor for poor prognosis in NRDS neonates (OR < 1, p < 0.05). The area under the curve of lung ultrasound scores combined with serum ANGPTL4 levels to assess the severity and prognosis of NRDS neonates exhibited a higher assessed value than the single test.Conclusion: Lung ultrasound scores and serum ANGPTL4 levels are closely related to the severity and prognosis of NRDS neonates, and the combination of the two improves the assessed value of the severity and prognosis of NRDS neonates. The study provided a reference for the disease severity assessment of NRDS and the prediction of its prognosis.Keywords: neonatal respiratory distress syndrome, lung ultrasound scores, angiopoietin-like protein 4, severity, prognosis